2016
DOI: 10.31018/jans.v8i3.953
|View full text |Cite
|
Sign up to set email alerts
|

Statistical media optimization studies for growth and polydroxybutyrate (PHB) production by Pseudomonas spp.

Abstract: Using glucose as carbon source and mustard cake and yeast extract as nitrogen sources bacterial isolate Pseudomonas B2 exhibited a maximum PHB recovery of 0.620 (in terms of O.D.) and PHB weight of 0.27g/L in 96 h. To determine the possibility of growth potential of Pseudomonas spp., it was grown in different carbon sources like fructose, glucose, maltose, mannitol etc. and it was found that glucose yielded good growth and PHB production. In order to incorporate cost effective nitrogen and carbon source, musta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…All of the regenerated samples showed all characteristic peaks corresponding to those observed for standard PHB indicating preservation of chemical structure during dissolution in the ILs. 18,29 However, it may be noted that the characteristic band of the CO streching vibration observed at 1724 cm −1 is a bit weaker in the case of the regenerated polymers in comparison to the standard sample, which is perhaps due to the interaction of the CO group with the cation of the ionic liquids having an amine group. Further molecular docking studies which are discussed later showed that the oxygen of (CO) tends to form H-bonding with the anions of ILs.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…All of the regenerated samples showed all characteristic peaks corresponding to those observed for standard PHB indicating preservation of chemical structure during dissolution in the ILs. 18,29 However, it may be noted that the characteristic band of the CO streching vibration observed at 1724 cm −1 is a bit weaker in the case of the regenerated polymers in comparison to the standard sample, which is perhaps due to the interaction of the CO group with the cation of the ionic liquids having an amine group. Further molecular docking studies which are discussed later showed that the oxygen of (CO) tends to form H-bonding with the anions of ILs.…”
Section: ■ Results and Discussionmentioning
confidence: 96%